Pneumatology the Holy Spirit in ecumenical, international, and contexual perspective - Kärkkäinen, Veli-Matti 1958- (Baker Academic, 2008)
Summary: One of the most exciting recent developments in theology has been an unprecedented interest in the person and work of the Holy Spirit. In fact, Veli-Matti Kärkkäinen describes this phenomenon as a "pneumatological renaissance." But such discussion should be informed, he contends, by two overarching principles. First, we must acknowledge the variety of approaches to the experience of the Holy Spirit ecumenically. Second, talk about the Spirit must always be contextual and therefore culture-specific. Working from this perspective, the book introduces readers to pneumatology, the theology and spirituality of the Holy Spirit, in current international theology. As such, the work offers a biblical, historical, and theological assessment of the Third Person of the Trinity and charts the various territories of contemporary writings and reflections on pneumatology.